INFLUENCE OF FAMILY SIZE AND AFTER SCHOOL ACTIVITIES ON STUDENTS’ ACADEMIC PERFORMANCE IN SURULERE AND KOSOFE LOCAL GOVERNMENT AREA OF LAGOS STATE - T., Omotayo O. (Sokoto Educational Review, 2020)
The paper researched into the influence of family size and after school activities on students’ academic performance in selected secondary schools in Surulere and Kosofe Local Government area of Lagos State. Four hypothesis were postulated in testing them, a questionnaire tagged Family Size on Academic Performance (FSAP) was designed and administered on 480 students in four public and four private schools through simple random sampling technique the collected data were analysed and interpreted using simple percentage, T-test and ANOVA Statistics. The result of the analysis revealed that there is significant difference in academic performance of students in public and private schools; differences in academic performance of large family and small family. Therefore it is recommended that Government among others should organize public lectures on family planning and public schools should endeavour to do their work conscientiously.